(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2020)
The State of Nicaragua emerged as an instrument of the elites of the dominant (Castilian) culture, to subdue the other cultures that existed at the arrival of the Europeans and that managed to survive the Castilian and English colonization. After the so-called independence of Central America, the Creole elites assumed the mission of giving it continuity and concluding the colonization project begun in the 16th century. With this purpose, they did everything to take power and design a state model capable of assuring their interests. For a century and a half, this political instrument of cultural domination worked effectively in all its components, but public education was the main vehicle of cultural submission, especially from the end of the 19th century. However, after the triumph of the Revolution in 1979, a true process of independence began, which covered all areas of society and culture was one of the fundamental pillars of the creation of a new society. Over the course of these four decades, a process of intercultural dialogue has been developing, from whichindigenous and Afro-descendant peoples have gradually made very significant progress in dismantling the republican colonial system. This decolonization process reaches its peak, with the Constitutional Reforms in February 2014, which include provisions that allow Nicaragua to be located as a Pluricultural State. In this work, we try to explain the development of this decolonization process, highlighting the role of Indigenous and Afro-descendant Peoples in the different historical moments.